Primeira década de Madrygal - Piñeiro Domínguez, María Jesús (Madrygal. Revista de Estudios Gallegos, 2008)
In ten years, Madrygal has become a core of the spreading of Galician culture. We offer a compilation of the contributions published throughout this decade full of excellent academic production.